2011
DOI: 10.1021/jp2073123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New ESIPT-Fluorescein: Photophysics of pH Sensitivity and Fluorescence

Abstract: ESIPT-inspired benzimidazolyl substituted fluorescein dyes were synthesized. PH-sensitivity was determined by the photophysical property measured at a physiological possible pH range. Fluorescence quantum efficiency values were calculated independently at two different emissions. A rational relationship is defined between fluorescence quantum efficiency and calculated HOMO energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 50 publications
0
29
0
4
Order By: Relevance
“…We have reported in our earlier communication that incorporation of an ESIPT unit in fluorescein causes a red shift in emission to the tune of 50 nm as compared to that of the original fluorescein (570 nm) [18,19].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have reported in our earlier communication that incorporation of an ESIPT unit in fluorescein causes a red shift in emission to the tune of 50 nm as compared to that of the original fluorescein (570 nm) [18,19].…”
Section: Introductionmentioning
confidence: 91%
“…In continuation of our work in benzimidazole, oxazole and thiazole chemistry [14,19,20] and to understand the effect of ESIPT unit in the photophysical properties of fluorescein moiety, in this paper, we report the synthesis and photophysical properties of novel fluorescein molecules containing thiazole units. The photophysical properties are studied as a function of pH and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In the excited state the proton may be transferred from amine group (NH) to keto group (C=O) through ESIPT process leads to the existence of both KHB and EHB forms [18][19][20][21][22][23]33]. In dual emission, the low intensity peak at 410 nm arises from the normal ketamine form and the red shifted high intensity peak at 435 nm corresponds to the stable tautomeric enolimine form.…”
Section: Electronic Emission Spectramentioning
confidence: 99%
“…This hypothesis leads to the concept of twisted intramolecular charge transfer (TICT) process. A number of reports have shown that the degree of steric hindrance plays an important role in dual emission arises from twisted intramolecular charge transfer (TICT) or excited state intramolecular proton transfer (ESIPT) process [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As a part of ongoing research to develop novel materials for high-tech applications (Sekar et al, 2010Gupta et al, 2011;Patil et al, 2012), here we report the synthesis, characterization, and photophysical properties of novel fluorescent biocompatible fluorophores and their binding study with protein. The novel triazine derivatives were prepared from 4-(4,6-dichloro-1,3,5-triazin-2-yl)-N,N -diethylaniline and different α -amino acids.…”
Section: Introductionmentioning
confidence: 99%